2010
DOI: 10.1002/hipo.20702
|View full text |Cite
|
Sign up to set email alerts
|

Functional emergence of the hippocampus in context fear learning in infant rats

Abstract: The hippocampus is a part of the limbic system and is important for the formation of associative memories, such as acquiring information about the context (e.g. the place where an experience occurred) during emotional learning (e.g. fear conditioning). Here, we assess whether the hippocampus is responsible for pups’ newly emerging context learning. In all experiments, postnatal day (PN) 21 and PN24 rat pups received 10 pairings of odor-0.5mA shock or control unpaired odor-shock, odor only and shock only. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 108 publications
(159 reference statements)
6
96
1
Order By: Relevance
“…This 'simulated poverty' induces stress in the dams (Ivy et al, 2008), and alters their behaviors (Ivy et al, 2008;Rice et al, 2008;Rincón-Cortés and Sullivan, 2014). This latter approach has provoked chronic unremitting stress in the pups (Gilles et al, 1996;Ivy et al, 2008;Rice et al, 2008;Moriceau et al, 2009;Raineki et al, 2010;Wang et al, 2011;Molet et al, 2014;Naninck et al, 2015). Notably, there is little evidence of physical stress of the pups, with no hypothermia and minimal weight changes .…”
Section: What Generates Stress Early In Life? Are the Consequences A mentioning
confidence: 99%
“…This 'simulated poverty' induces stress in the dams (Ivy et al, 2008), and alters their behaviors (Ivy et al, 2008;Rice et al, 2008;Rincón-Cortés and Sullivan, 2014). This latter approach has provoked chronic unremitting stress in the pups (Gilles et al, 1996;Ivy et al, 2008;Rice et al, 2008;Moriceau et al, 2009;Raineki et al, 2010;Wang et al, 2011;Molet et al, 2014;Naninck et al, 2015). Notably, there is little evidence of physical stress of the pups, with no hypothermia and minimal weight changes .…”
Section: What Generates Stress Early In Life? Are the Consequences A mentioning
confidence: 99%
“…Whereas pre-weanling (P17) rats do not appear to extend learned fear associations to the broader surrounding environment, adult-like contextual fear conditioning emerges by P24. The emergence of contextual fear learning may reflect increased maturation of the hippocampus and its connections to the amygdala in the post-weanling animals (Raineki et al, 2010). Contextual fear memories in this juvenile, pre-adolescent phase are also labile, and undergo forgetting with the passage of time (Akers et al, 2014).…”
Section: Developmental Changes In Fear-learning Circuitsmentioning
confidence: 99%
“…Both the amygdala and the hippocampus are involved in contextual conditioning (Anagnostaras et al, 2001;LeDoux, 2000b;Matus-Amat et al, 2007;Wiltgen et al, 2006). It has been shown that conditioning to a context emerges between 17 and 24 days of age in rats (Foster and Burman, 2010;Raineki et al, 2010;Rudy, 1993). Interestingly, however, whereas the hippocampus is not activated during such context conditioning in 21-day-old rats, it is activated in 24-dayolds (Raineki et al, 2010).…”
Section: Functional Considerationsmentioning
confidence: 99%
“…It has been shown that conditioning to a context emerges between 17 and 24 days of age in rats (Foster and Burman, 2010;Raineki et al, 2010;Rudy, 1993). Interestingly, however, whereas the hippocampus is not activated during such context conditioning in 21-day-old rats, it is activated in 24-dayolds (Raineki et al, 2010). The emergence of contextual conditioning is thus likely related to the maturation of both the hippocampus, which also exhibits a delayed developmental profile (Bekenstein and Lothman, 1991;Jabès et al, 2010Jabès et al, , 2011Nurse and Lacaille, 1999;Swann et al, 1990), and the basolateral complex of the amygdala, which likely is insufficiently mature to integrate such contextual information until the beginning of the third week of life.…”
Section: Functional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation